Mind Re-ascribed - Mölder, Bruno (Studia Philosophica Estonica, 2017)
This paper is a reply to commentaries on Mind Ascribed. My response is organised into three parts. In the first part I describe the relationship between folk psychology and the scientific study of the mind. The second part replies to objections to the central tenets and presuppositions of the ascription theory. I clarify the distinction between the nature and the possession of mental states and the notion of a pleonastic entity. I explain why the ascription theory is a version of interpretivism, and not a species of instrumentalism or fictionalism. I also argue that canonical ascription should not be spelled out in terms of the ideal interpreter. The third part deals with comments on miscellaneous topics such as normativity, self-knowledge, the necessity of the brain and the proper understanding of intentional patterns.